2006
DOI: 10.1021/jp055342b
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Microkinetic Approach of the Photocatalytic Oxidation of Isopropyl Alcohol on TiO2. Part 1. Surface Elementary Steps Involving Gaseous and Adsorbed C3HxO Species

Abstract: The present study concerns an experimental microkinetic approach of the photocatalytic oxidation (PCO) of isopropyl alcohol (IPA) into acetone on a pure anatase TiO2 solid according to a procedure previously developed. Mainly, the kinetic parameters of each surface elementary step of a plausible kinetic model of PCO of IPA are experimentally determined: natures and amounts of the adsorbed species and rate constants (preexponential factor and activation energy). The kinetics parameters are obtained by using exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
143
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(154 citation statements)
references
References 39 publications
11
143
0
Order By: Relevance
“…The adsorption of IPA on TiO2 surface leads to the formation of three surface species. The formation of monodentate isopropoxy groups and surface hydroxyl species indicates dissociative adsorption of IPA through Equation (2) [54], the authors proposed that acetone, produced from oxidation of adsorbed IPA on S(1) sites, could not remain adsorbed on similar adsorption sites (due to competitive adsorption phenomena between IPA and acetone). Acetone either rapidly desorbed to the gas phase if no surface sites denoted by S(2) were available or diffused toward an available S(2) site.…”
Section: Sequential Treatment (Adsorption Followed By Ntp Oxidation)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adsorption of IPA on TiO2 surface leads to the formation of three surface species. The formation of monodentate isopropoxy groups and surface hydroxyl species indicates dissociative adsorption of IPA through Equation (2) [54], the authors proposed that acetone, produced from oxidation of adsorbed IPA on S(1) sites, could not remain adsorbed on similar adsorption sites (due to competitive adsorption phenomena between IPA and acetone). Acetone either rapidly desorbed to the gas phase if no surface sites denoted by S(2) were available or diffused toward an available S(2) site.…”
Section: Sequential Treatment (Adsorption Followed By Ntp Oxidation)mentioning
confidence: 99%
“…Noting that only a small fraction of TiO2 surface sites S(2) are specific to the acetone adsorption (there is no competitive chemisorption with IPA). For IPA, literature data [54][55][56] strongly suggest that acetone is the single route to produce CO2 and H2O. Experiments have revealed that when the TiO2 surface is fully saturated with IPA, small amounts of S(2) sites are accessible for irreversibly adsorbed acetone and its subsequent oxidation into CO2 [51].…”
Section: Sequential Treatment (Adsorption Followed By Ntp Oxidation)mentioning
confidence: 99%
“…During the reaction a consecutive reduction of the intensity of the n(O-O) vibration of the peroxo group is observed, which [22,23]. The band at 1734 cm À1 is assigned to the n(CO) vibration of acetone [9,24,25].…”
mentioning
confidence: 99%
“…For GaN/ZnO solid solution, the IPA photodegradation process is much more complex as described in processes (3)- (8): both e − and h + are very active simultaneously. [27][28][29] Figure 6 schematically illustrates the whole reaction mechanisms of IPA photodegradation over ZnO, GaN, and GaN/ZnO solid solution, respectively.…”
mentioning
confidence: 99%